College student motivational determinants for combining alcohol and energy drinks: Early identification could be the key. (February 2014) - Kensinger, Weston; Woolsey, Conrad; Divin, Amanda; Tapps, Tyler
<x xml:space="preserve">Abstract</x> Aims: Strategic energy drink marketing continues to target college students despite this group already being identified as high-risk for experiencing negative consequences. To better understand and predict drinking behaviors and to develop more effective prevention programs, this study examined students alcohol-only and combined-use positive drinking motives within subjects. Methods: A convenience sample of college students (n = 540) from a university in the Southwest United States voluntarily completed an online version of the Drinking Motives Questionnaire-Revised (α = 0.96) to explore motives for consuming alcohol only and alcohol combined with energy drinks. Findings: Results indicate college students who combine alcohol and energy drinks have more positive drinking motives than those who consume alcohol-only. Conclusions: Positive drinking motivational determinants can be used to improve existing prevention programs and to help practitioners work more effectively with students to address alternative ways to achieve the desired social and cognitive effects of drinking.